Combining Edible Coatings Technology and Nanoencapsulation for Food Application: A Brief Review with an Emphasis on Nanoliposomes - Osorio-Lira, F; Lopez-Polo, J; Monasterio-Aranda, A (Elsevier Ltd, 2021)
The use of bioactive compounds within the biopolymer-based Edible Coatings (EC) matrices has certain limitations for their application at the food industry level. Encapsulation has been considered as a strategy that enables protecting and improving the physical and chemical characteristics of the compounds; as a result, it extends the shelf life of coated foods. This review discusses recent progress in combining edible coatings with nanoencapsulation technology. We also described and discussed various works, in which nanoliposomes are used as encapsulation systems to prepare, and subsequently apply the edible coatings in plant products and meat products. The use of nanoliposomes for the encapsulation of phenolic compounds and essential oils provides an improvement in the antioxidant and antimicrobial properties of coatings by extending the shelf life of food matrices. However, when liposomes are stored for a long period of time, they may present some degree of instability manifested by an increase in size, polydispersity index, and zeta potential. This is reflected in an aggregation, fusion, and rupture of the vesicles. This investigation can help researchers and industries to select an appropriate and efficient biopolymer to form EC containing nanoencapsulated active compounds. This work also addresses the use of nanoliposomes to create EC extending markedly the shelf life of fruit, reducing the weight loss, and deterioration due to the action of microorganisms. © 2021 Elsevier Ltd
Keywords: Edible materials; Encapsulation; Active compound; Biopolymers; Food matrices; Shelf life